Naming Africans: On the Epistemic Value of Names, Oyeronke Oyewumi and Hewan Girma (eds.) Switzerland: Palgrave Macmillan, 2023. 237 pages. 129.99 - BERNARD, Oluwabunmi Tope (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
My name is Olúwábùnmi Tèmítọ́pẹ́ which means “God has given (this child) to me, I am grateful.” Both of my names were given to me by my mother, who had me through a Caesarean Section (CS). So, my first name came from her experience during pregnancy and my second name was her way of showing gratitude for surviving her near-death childbirth experience. She told me she was grateful that she regained consciousness almost four (4) weeks after my birth. Like me, all my siblings had names that marked important, memorable events in our parents’ lives. Our names tell our parents’ stories, stories about circumstances surrounding our births, rather than our stories as may be found in many brief personal oríkì (praise names) among the Ọ̀yọ́-Yorùbá. For many of us whose parents are from Ondo and Ekiti States of Nigeria, we do not have brief personal oríkì as noted by Ladele, et. al. and quoted by Oyewumi, p.21, but parents still gave very specific Àmútọ̀runwá[2] names “whose chief distinction is that they are based on the observed biological facts attending the birth of that child”[3] which is a common phenomenon in Yorùbá culture. African names reveal a lot about the bearer’s background and carry “a wealth of historical information.” Caesarean sections or Caesarean deliveries are surgical procedures by which babies are born through incisions in their mothers’ abdomen and uterus. Even though the technique dates to 1480 CE, it has since then evolved and has been improved on to reduce mother and child mortality rate. Still, in the early 80s at the time of my birth, the Caesarean technique was still very risky and many things could and do go wrong. In my mother’s case, things went wrong with the procedure. Because of that, she was unconscious from the procedure for almost a month. There are very few Àmútọ̀runwá (brought from ọ̀run (invisible realm)) names among the Yorùbá. They are Táyé, Kẹhinde, Ìdòwú, Àlàbá, Okẹ́, Ìgè, Àìná, Òjó, and a few others. These names have not changed. Some of them are gender neural while others are gender specific. For example, Táyé and Kẹhìndé are gender neutral names for twins regardless of their genders. En caul births are called Okẹ́ and breech babies are called Ìgè regardless of their genders. Àìná and Òjó are examples of gender specific names. Àìná is a female child born with nuchal cords while Òjó is a male child born with the same condition.